Spiritual Education in the Qur’an: A Study of the Concept of Tasbih and Its Relevance to the Formation of Muslim Character - Maswan Ahmadi; Mardan Mardan; Muhsin Mahfud (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study aims to analyze the concept of tasbih in the Qur'an and its relevance to the formation of a Muslim's spiritual character through a thematic Qur'anic interpretation approach. The study employed a qualitative approach using a library research method. Data were collected by identifying Qur'anic verses related to tasbih and analyzed based on the interpretations of classical and contemporary exegetes, relevant hadiths, and scholarly literature. The findings reveal that tasbih in the Qur'an is not merely a form of verbal remembrance but also represents the glorification and transcendence of Allah, acknowledgment of His greatness, the obedience of all creation to Allah, and serves as a foundation for spiritual education. These values of tasbih are relevant to fostering the spiritual character of Muslims by cultivating faith, piety, humility, discipline in worship, and a constant awareness of remembering and glorifying Allah in every aspect of life.